VERTICAL GARDEN MEWUJUDKAN SEKOLAH DASAR BERBASIS LINGKUNGAN - Abdulrasyid Tolangara; Rohima Wahyu Ningrum (IKIP PGRI Bojonegoro, 2018)
ABSTRACTSchool yard is the most appropriate learning media to support learning creativity for learners. The narrow use of school yard has not been well implemented so that the students' ignorance towards the environment is closely related to the decreasing environmental quality in schools. To improve the quality of education and learning achievement of learners about environmental knowledge can provide a direct understanding to learners about the environment by applying the concept of vertical garden in the yard of the school. Vertical concept of this garden becomes an alternative in getting around the yard or narrow land. The school plays an important role in this devotion program at the time of making the garden vertical garden, where the school proposes the implementation of maintenance activities and planting new plant species in the annual plan of SDN 34 Kota Ternate. Socialization and workshops that have been done with the school together with community service team Unkhair can provide an early description of the use of a narrow school yard by applying the garden vertical garden. Another target of this program is that students and teachers feel the benefits of this school park in classroom learning so that they can apply the concept of farming obtained for the home.Keywords: Garden vertical garden, environment, school yard.ABSTRAKPekarangan sekolah merupakan media belajar yang paling tepat untuk menunjang kreativitas belajar bagi peserta didik. Pemanfaatan pekarangan sekolah yang sempit masih belum terlaksana dengan baik sehingga ketidakpedulian peserta didik terhadap lingkungan sangat berkaitan dengan menurunnya kualitas lingkungan di sekolah. Untuk dapat meningkatkan kualitas pendidikan dan prestasi belajar peserta didik tentang pengetahuan lingkungan dapat memberi pemahaman langsung kepada peserta didik tentang lingkungan hidup dengan menerapkan konsep vertical garden di pekarangan sekolah. Konsep vertikal garden ini menjadi sebuah alternatif dalam menyiasati pekarangan atau lahan yang sempit. Pihak sekolah sangat berperan penting dalam program pengabdian ini pada saat pembuatan taman vertical garden, dimana pihak sekolah mengusulkan pelaksanaan kegiatan perawatan dan penanaman jenis tanaman baru dalam rencana tahunan SDN 34 Kota Ternate. Sosialisasi dan workshop yang telah dilakukan bersama pihak sekolah bersama tim pengabdian masyarakat Unkhair dapat memberikan gambaran awal tentang pemanfaatan pekarangan sekolah yang sempit dengan menerapkan taman vertical garden. Target lain luaran program ini adalah diharapkan peserta didik dan guru merasakan manfaat dari taman sekolah ini pada pembelajaran di kelas sehingga dapat menerapkan konsep bercocok tanam yang diperoleh untukÂ dirumah. Â Kata Kunci: Taman vertical garden, lingkungan, pekarangan sekolah.